Exploiting the Prisoner's Efficiency Under Modern Criminal Policy - Bakel, Ali (Journal of Legal Studies and Researches, 2017)
The evolving methods of committing crimes in their various forms reflect the high level of their perpetrators, necessitating deterrence, often through imprisonment. However, imprisonment has detrimental effects on both the state and the prisoner. This situation has led to a search for alternative sentences that contribute to the social and psychological rehabilitation of prisoners and redirect their abilities for the benefit of society. Algerian legislation has tentatively adopted community service, but this sentence is met with considerable reluctance due to the conditions and procedures of its application, which are incompatible with the exemplary use of the prisoner's capabilities.